Outcomes of vertebroplasty compared with kyphoplasty: a systematic review and meta-analysis. (11th May 2015) - Gu, Chris N; Brinjikji, Waleed; Evans, Avery J; Murad, Mohammad H; Kallmes, David F
Abstract : Background and purpose: Many studies demonstrate that both kyphoplasty and vertebroplasty are superior to conservative therapy in the treatment of osteoporotic vertebral body compression fractures. We performed a systematic review and meta-analysis of studies comparing the outcomes of vertebroplasty and kyphoplasty, which included prospective non-randomized, retrospective comparative, and randomized studies. Materials and methods: We searched MEDLINE, EMBASE, and the Web of Science databases for studies of kyphoplasty versus vertebroplasty from 1 January 1990 to 30 November 2014 and compared the following outcomes: procedure characteristics, pain and disability improvement, complications and anatomic outcomes. A subgroup analysis was performed comparing pain outcomes based on the risk of bias. Results: 29 studies enrolling 2838 patients (1384 kyphoplasty and 1454 vertebroplasty) were included. 16 prospective non-randomized studies, 10 retrospective comparative studies, and 3 randomized controlled studies were included. No significant differences were found in mean pain scores between the two groups postoperatively (2.9±1.5 kyphoplasty vs 2.9±1.7 vertebroplasty, p=0.39) and at 12 months (2.7±1.8 kyphoplasty vs 3.2±1.8 vertebroplasty, p=0.64). No significant differences were found in disability postoperatively (34.7±7.1 kyphoplasty group vs 36.3±7.8 vertebroplasty group, p=0.74) or at 12 months (28.3±16 kyphoplasty group vs 29.6±13.9 vertebroplasty group, p=0.70). Kyphoplasty was associated with lower odds of new fractures (p=0.06), less extraosseous cement leakage (p<0.01), and greater reduction in kyphotic angle (p<0.01). Conclusions: No significant difference was found between vertebroplasty and kyphoplasty in short- and long-term pain and disability outcomes. Further studies are needed to better determine if any particular subgroups of patients would benefit more from vertebroplasty or kyphoplasty in the treatment of vertebral body compression fractures.